2019
DOI: 10.1007/s13361-019-02167-w
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Qualitative and Quantitative Top-Down Proteomics Using Capillary Zone Electrophoresis-Electrospray Ionization-Tandem Mass Spectrometry with Nanograms of Proteome Samples

Abstract: Capillary zone electrophoresis-electrospray ionization-tandem mass spectrometry (CZE-ESI-MS/MS) has attracted attention recently for top-down proteomics because it can achieve highly efficient separation and very sensitive detection of proteins. However, separation window and sample loading volume of CZE need to be boosted for a better proteome coverage using CZE-MS/MS. Here, we present an improved CZE-MS/MS system that achieved a 180-min separation window and a 2-μL sample loading volume for top-down characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 42 publications
(67 reference statements)
0
72
0
Order By: Relevance
“…Such focusing is generally utilized for analysis of peptides and intact proteins by CE-MS, and achieved by generating a pH-induced electrophoretic mobility variation at the sample/pH barrage boundary. It has been successfully applied for the study of the MCF7 breast cancer cell proteome using the bottom-up approach [10], and for top-down proteomic analysis of the zebrafish brain cerebellum (Cb) and optic tectum (Teo) regions [11]. Also, quantitative analysis of bisphosphonate compounds [12] and digested monoclonal antibodies [13] was achieved by this technique.…”
Section: Sample Preconcentrationmentioning
confidence: 99%
“…Such focusing is generally utilized for analysis of peptides and intact proteins by CE-MS, and achieved by generating a pH-induced electrophoretic mobility variation at the sample/pH barrage boundary. It has been successfully applied for the study of the MCF7 breast cancer cell proteome using the bottom-up approach [10], and for top-down proteomic analysis of the zebrafish brain cerebellum (Cb) and optic tectum (Teo) regions [11]. Also, quantitative analysis of bisphosphonate compounds [12] and digested monoclonal antibodies [13] was achieved by this technique.…”
Section: Sample Preconcentrationmentioning
confidence: 99%
“…[18][19][20][21][22] The data clearly demonstrate the power of our CZE-MS/MS-based TDP workflow for comprehensive characterization of proteoforms in complex proteome samples. We attribute the drastic improvement of proteoform IDs to the high separation efficiency of CZE for proteoforms, [23] high sensitivity of CZE-MS for proteoform detection, [23][24][25] and high orthogonality of LC and CZE for biomolecule separations. [21,26] The features of CZE-MS/MS for TDP have been systematically reviewed recently.…”
Section: Deep Tdp Of Human Colorectal Cancer Cell Lines-pagementioning
confidence: 99%
“…Quantitative information was based on the relative intensities of the detected glycoforms where glycoform concentrations were estimated to range between 0.35 and 630 nM. In a TDMS study, Lubeckyj et al () demonstrated a label‐free strategy for the quantification of thousands of proteoforms from zebrafish brain using CZE‐MS. This quantitative approach revealed that the abundance of proteoforms differs significantly in different regions of the zebrafish brain.…”
Section: Capillary Electrophoresis‐mass Spectrometrymentioning
confidence: 99%